(2, J)-IDEALS IN COMMUTATIVE RINGS - (:unkn) unknown (PUBL HOUSE BULGARIAN ACAD SCI, 2020)
Let A be a commutative ring with nonzero identity. In this paper, we introduce the concept of (2, J)-ideal as a generalization of J-ideal. A proper ideal P of A is said to be a (2, J)-ideal if whenever abc is an element of P and a, b, c is an element of A, then ab is an element of P or ac is an element of Jac(A) or be is an element of Jac(A). Various examples and characterizations of (2, J)-ideals are given. Also, we study many properties of (2, J)-ideals and use them to characterize certain classes of rings such as quasi-local rings and Artinian rings.
Keywords: ideal; J-ideal; (2, J)-ideal; (2, n)-ideal; 2-ABSORBING PRIMARY IDEALS